Digital Migration and its Impact on the Programming of State Broadcaster: Case of Radio Pakistan - Sheikh, Muhammad Ahmad; Yousaf, Zahid; Yousaf, Muhammad; Kiran, Ayesha (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigates Radio Pakistan's digital transition and its effects on programming. Radio Pakistan has embraced digital migration as a result of the quick transformation of traditional broadcasting methods brought about by the arrival of digital technologies. This change involves transmitting in analog to digital format and integrating digital content delivery channels including podcasts, internet radio, and mobile apps. The study looks at how the shift to digital media has affected programming approaches, with a particular emphasis on content variety. Besides, paper discusses how diverse technological evolutions have shaped public perception in a constructive way and what role Radio Pakistan, as a public broadcaster, has played in this regard. The paper also looks at the reasons for the paradigm shift of the broadcast media industry from analogue culture to a contemporary digital world through an extensive literature review and theoretical analysis using interview guide a tool of data collection. The study provides guidelines to policy makers of Radio Pakistan, executive of a community radio station, a media educator of Pakistan to understand the affected by these historic developments and expedite the expansion of DRM plan which is underway with slowest pace.